High temperature quasistatic and dynamic mechanical behavior of interconnected 3D carbon nanotube structures. (February 2019) - Bhowmick, Sanjit; Ozden, Sehmus; Bizão, Rafael A.; Machado, Leonardo Dantas; Asif, S.A. Syed; Pugno, Nicola M.; Galvão, Douglas S.; Tiwary, Chandra Sekhar; Ajayan, P.M.
Abstract: Carbon nanotubes (CNTs) are one of the most appealing materials in recent history for both research and commercial interest because of their outstanding physical, chemical, and electrical properties. This is particularly true for 3D arrangements of CNTs which enable their use in larger scale devices and structures. In this paper, the effect of temperature on the quasistatic and dynamic deformation behavior of 3D CNT structures is presented for the first time. An in situ high-temperature nanomechanical instrument was used inside an SEM at high vacuum to investigate mechanical properties of covalently interconnected CNT porous structures in a wide range of temperature. An irreversible bucking at the base of pillar samples was found as a major mode of deformation at room and elevated temperatures. It has been observed that elastic modulus and critical load to first buckle formation decrease progressively with increasing temperature from 25 °C to 750 °C. To understand fatigue resistance, pillars made from this unique structure were compressed to 100 cycles at room temperature and 750 °C. While the structure showed remarkable resistance to fatigue at room temperature, high temperature significantly lowers fatigue resistance. Molecular dynamics (MD) simulation of compression highlights the critical role played by covalent interconnections which prevent localized bending and improve mechanical properties. Graphical abstract: Image 1 An in situ high-temperature nanomechanical instrument was used inside an SEM at high vacuum to investigate properties of covalently interconnected CNT porous structures in a wide range of temperature. An irreversible buckling at the base of pillar samples was found as a major mode of deformation at room and elevated temperatures. We report the variation of elastic modulus, critical load to first buckle formation and other change in mechanical properties as a function of temperature. We also showed a remarkable fatigue resistance of CNTs at room temperature and a gradual change in resistance at high temperature. Molecular dynamics (MD) simulation of compression highlights the critical role played by covalent interconnections which prevent localized bending and improved mechanical properties.